Polyurethane electronic glue containing n-hexane and preparation method thereof

By adding flame retardant and thermal filler and foaming microcapsules to the polyurethane electronic glue, the problem of poor thermal conductivity after foaming of the polyurethane electronic glue is solved, and efficient heat dissipation and good flame retardant performance are achieved.

CN119529744AInactive Publication Date: 2025-02-28东营市润泽新材料有限公司

Patent Information

Application Number
CN202510094432.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent
Patent Text Reader

Abstract

The invention relates to the technical field of electronic adhesives, in particular to an n-hexane-containing polyurethane electronic adhesive and a preparation method thereof.The n-hexane-containing polyurethane electronic adhesive is prepared from, by weight, 40-45 parts of polyether polyol, 25-30 parts of polypropylene glycol, 35-40 parts of isocyanate, 1-2 parts of 1, 4-butanediol, 0.02-0.03 part of a catalyst, 6-7 parts of flame-retardant heat-conducting filler, 1.2-1.5 parts of foaming microcapsules and 1-2 parts of a foam stabilizer; by adding the flame-retardant heat-conducting filler and the foaming microcapsule taking normal hexane as a core, the problem that the existing polyurethane electronic glue is poor in heat-conducting property after foaming is solved, and meanwhile, the polyurethane electronic glue also has good flame-retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic adhesives, and in particular to polyurethane electronic adhesive containing n-hexane and a preparation method thereof. Background Art

[0002] With the rapid development of electronic integration technology, the heat dissipation problem of electronic components has become increasingly prominent. Ordinary electronic potting glue has low thermal conductivity and cannot dissipate heat quickly. At the same time, with the development of the times, new requirements are also put forward for the weight of electronic products. Therefore, foaming agents are added to the electronic potting glue to make it foam and reduce the weight. However, the foaming structure further leads to a decrease in the thermal conductivity of the electronic potting glue, which greatly affects the use of electronic products and can no longer meet market demand. Summary of the invention

[0003] The purpose of the present invention is to provide a polyurethane electronic adhesive containing n-hexane and a preparation method thereof. By adding flame-retardant thermal conductive fillers and foaming microcapsules with n-hexane as the core, the problem of poor thermal conductivity of the existing polyurethane electronic adhesive after foaming is solved, and the polyurethane electronic adhesive also has good flame retardant properties.

[0004] The object of the present invention can be achieved by the following technical scheme: a method for preparing a polyurethane electronic adhesive containing n-hexane, comprising the following steps: weighing the following raw materials in parts by weight: 40-45 parts of polyether polyol, 25-30 parts of polypropylene glycol, 35-40 parts of isocyanate, 1-2 parts of 1,4-butanediol, 0.02-0.03 parts of catalyst, 6-7 parts of flame retardant thermal conductive filler, 1.2-1.5 parts of foaming microcapsules and 1-2 parts of foam stabilizer; mixing the polyether polyol, polypropylene glycol, isocyanate, 1,4-butanediol, catalyst, flame retardant thermal conductive filler, foaming microcapsules and foam stabilizer, stirring at a stirring rate of 120 rpm and a temperature of 40°C to prepare a polyurethane electronic adhesive containing n-hexane; The polyether polyol is Tangyi RHEOLATE 350D polyether polyol; The polypropylene glycol is Huaxiang PPG-1000 polypropylene glycol; The isocyanate is Wanhua WXB-20180516 isocyanate; The catalyst is Kairui T12 catalyst; The foam stabilizer is Fidelity CAB-35 foam stabilizer; The flame retardant thermal conductive filler is prepared by the following steps: Step A1: Boron nitride, urea and deionized water are mixed and added to a ball mill, and ball milled for 8-10 hours at a rotation speed of 800 rpm to obtain a precursor 1, graphene oxide and deionized water are mixed and ultrasonically dispersed for 30 minutes, sodium carbonate solution is added to adjust the pH value to 8, and precursor 1, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide are added under stirring at a stirring rate of 300-340 rpm and a temperature of 40°C, and reacted for 12-14 hours to obtain a precursor 2; The dosage ratio of boron nitride, urea and deionized water is 2.4-2.6g:80-90g:150-160mL; the mass fraction of sodium carbonate solution is 15%, and the dosage ratio of graphene oxide, deionized water, precursor 1, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide is 1.4-1.5g:150-180mL:2.4-2.6g:1.1-1.2g:1.4-1.5g; During the reaction, urea enters the interlayer of boron nitride through ball milling to exfoliate and modify it, thereby obtaining amino-functionalized precursor 1. Then, under the action of N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide, the amino groups in precursor 1 react with the oxygen-containing groups in graphene oxide to form a layered structure connected by covalent bonds, thereby obtaining precursor 2. Step A2: 1-vinylimidazole and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (abbreviation: DOPO) were mixed, and the mixture was reacted for 12 hours at a stirring rate of 140-160 rpm and a temperature of 140° C., and then tannic acid, Tris-HCl buffer and ethanol solution were added, and the mixture was cooled to room temperature and continued to react for 3-4 hours, and then ferric chloride and precursor 2 were added and reacted for 12 hours to obtain a flame retardant thermal conductive filler; The mass fraction of the ethanol solution is 15%, the pH value of the Tris-HCl buffer is 8, and the amount ratio of 1-vinylimidazole, DOPO, tannic acid, Tris-HCl buffer, ethanol solution, ferric chloride and precursor 2 is 0.01-0.011 mol: 0.011 mol: 6.5-6.8 g: 60-70 mL: 140-150 mL: 1.9-2.2 g: 3.4-3.5 g; During the reaction, DOPO reacts with the double bond in 1-vinyl imidazole to obtain a nitrogen-phosphorus addition product, and then tannic acid and Tris-HCl buffer are added to polymerize the addition product through hydrogen bonding between tannic acid and the addition product. Ferric chloride is then added to form a complex on the surface of the precursor 2 through the complexation between the iron ions and the tannic acid, thereby obtaining a flame-retardant thermal conductive filler. The foamed microcapsules are prepared by the following steps: Step B1: 1-vinylimidazole and n-butyl bromide are mixed, and the mixture is reacted for 24 hours at a stirring rate of 120-140 rpm and a temperature of 80°C to obtain an intermediate a; the intermediate a, alanine and deionized water are mixed, and the mixture is stirred for 24 hours at a stirring rate of 240-260 rpm and room temperature to obtain an intermediate b; carbon nanotubes, intermediate b and toluene are mixed and ultrasonically dispersed for 30 minutes, and the mixture is reacted for 24 hours at a stirring rate of 500-550 rpm and a temperature of 90°C to obtain modified carbon nanotubes; The dosage ratio of 1-vinylimidazole and n-butane bromide is 0.15-0.16 mol: 0.17-0.18 mol; the dosage ratio of intermediate a, alanine and deionized water is 0.1-0.11 mol: 0.11 mol: 40-50 mL; the dosage ratio of carbon nanotubes, intermediate b and toluene is 5.7-5.8 g: 0.6-0.8 g: 50-60 mL; During the reaction, the imidazole structure in 1-vinyl imidazole reacts with bromine in n-butane bromide to form an imidazolium structure to obtain an intermediate a, and the intermediate a then undergoes an ion exchange reaction with alanine to obtain an intermediate b, and then the modified carbon nanotubes are obtained through the π-π interaction between the imidazolium structure in the intermediate b and the carbon nanotubes; Step B2: Mix branched polyether polyol, polyethylene glycol, 1,4-butanediol and isophorone diisocyanate, react for 3-4 hours at a stirring rate of 120-140 rpm and a temperature of 90°C, then add hexamethylene diisocyanate, triethylamine and n-hexane, and continue stirring for 30 minutes at a stirring rate of 240-280 rpm and a temperature of 50°C, then add deionized water and continue stirring for 30 minutes to obtain a dispersion system, mix modified carbon nanotubes, diethylenetriamine and deionized water, stir at a stirring rate of 80-100 rpm and room temperature, add to the dispersion system, react for 3-4 hours, and obtain foaming microcapsules; The amount ratio of branched polyether polyol, polyethylene glycol, 1,4-butanediol, isophorone diisocyanate, hexamethylene diisocyanate, triethylamine, n-hexane and deionized water is 0.4-0.5g: 1-1.1g: 1.1-1.2g: 6.5-7.2g: 4.5-4.8g: 0.7-0.75g: 4.2-4.5g: 70-75mL; the amount ratio of modified carbon nanotubes, diethylenetriamine, deionized water and dispersion system is 3.4-3.6g: 4.2-4.3g: 15-18mL: 70-75mL; During the reaction, the isocyanate groups in isophorone diisocyanate react with the hydroxyl groups in branched polyether polyol, polyethylene glycol and 1,4-butanediol to form a prepolymer, and then hexamethylene diisocyanate, n-hexane and water are added to form a dispersion with n-hexane as the core and the prepolymer as the shell through its self-emulsification characteristics, and then modified carbon nanotubes and diethylenetriamine are added, and the amino groups in the modified carbon nanotubes and diethylenetriamine react with the isocyanate groups on the shell of the dispersion to form a double-layer shell structure, thereby preparing foaming microcapsules; Beneficial effects of the invention: The invention discloses a polyurethane electronic adhesive containing n-hexane and a preparation method thereof. By adding flame-retardant thermal conductive fillers and foaming microcapsules with n-hexane as the core, the problem of poor thermal conductivity of the existing polyurethane electronic adhesive after foaming is solved. At the same time, it also has good flame retardant properties. The flame retardant thermal conductive filler is connected to the surface of the precursor 2 through complexation and non-covalent bonds to form an iron complex. The complexed iron ions cooperate with the phosphorus-nitrogen flame retardant system to play a good flame retardant role. At the same time, the matrix itself can also be used as a flame retardant filler to form a denser carbon layer, further improving the flame retardant performance. The surface of the foamed microcapsules is connected with modified carbon nanotubes through isocyanate, which changes the pressure resistance and sealing performance of the microcapsules. During the foaming process, the n-hexane core material of the foamed microcapsules is heated, which increases the volume of the foamed microcapsules and forms a foamed structure. The improvement of the pressure resistance and sealing performance can also prevent the foamed microcapsules from being damaged during the foaming process and causing the leakage of n-hexane. At the same time, the microcapsule shell has certain thermal conductivity. Since the flame retardant thermal conductive filler itself is a layered structure, they cooperate with each other to form a three-dimensional thermal conductive path, thereby greatly improving the thermal conductivity of the polyurethane electronic adhesive. DETAILED DESCRIPTION

[0005] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0006] Example 1 A method for preparing a polyurethane electronic adhesive containing n-hexane, comprising the following steps: weighing the following raw materials in parts by weight: 40 parts of polyether polyol, 25 parts of polypropylene glycol, 35 parts of isocyanate, 1 part of 1,4-butanediol, 0.02 parts of catalyst, 6 parts of flame retardant thermal conductive filler, 1.2 parts of foaming microcapsules and 1 part of foam stabilizer; mixing the polyether polyol, polypropylene glycol, isocyanate, catalyst, flame retardant thermal conductive filler, foaming microcapsules and foam stabilizer, stirring at a stirring rate of 120 rpm and a temperature of 40° C. to prepare a polyurethane electronic adhesive containing n-hexane; The polyether polyol is Tangyi RHEOLATE 350D polyether polyol; The polypropylene glycol is Huaxiang PPG-1000 polypropylene glycol; The isocyanate is Wanhua WXB-20180516 isocyanate; The catalyst is Kairui T12 catalyst; The foam stabilizer is Fidelity CAB-35 foam stabilizer; The flame retardant thermal conductive filler is prepared by the following steps: Step A1: Mix commercially available Ruihuang Metal 1000 mesh boron nitride, urea and deionized water and add them to a ball mill, and ball mill for 8 hours at a rotation speed of 800 rpm to obtain precursor 1, mix graphene oxide and deionized water and ultrasonically disperse for 30 minutes, add sodium carbonate solution to adjust the pH value to 8, stir at a stirring rate of 300 rpm and a temperature of 40°C, stir and add precursor 1, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide, and react for 12 hours to obtain precursor 2; The dosage ratio of boron nitride, urea and deionized water is 2.4g:80g:150mL; the mass fraction of sodium carbonate solution is 15%, and the dosage ratio of graphene oxide, deionized water, precursor 1, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide is 1.4g:150mL:2.4g:1.1g:1.4g; Step A2: 1-vinylimidazole and DOPO were mixed, and the mixture was reacted for 12 hours at a stirring rate of 140 rpm and a temperature of 140° C., and then tannic acid, Tris-HCl buffer and ethanol solution were added, and the mixture was cooled to room temperature and the reaction was continued for 3 hours, and then ferric chloride and precursor 2 were added and the reaction was continued for 12 hours to obtain a flame retardant thermal conductive filler; The mass fraction of the ethanol solution is 15%, the pH value of the Tris-HCl buffer is 8, and the amount ratio of 1-vinylimidazole, DOPO, tannic acid, Tris-HCl buffer, ethanol solution, ferric chloride and precursor 2 is 0.01 mol: 0.011 mol: 6.5 g: 60 mL: 140 mL: 1.9 g: 3.4 g; The foamed microcapsules are prepared by the following steps: Step B1: 1-vinylimidazole and n-butyl bromide were mixed, and the mixture was reacted at a stirring rate of 120 rpm and a temperature of 80°C for 24 hours to obtain intermediate a. Intermediate a, alanine and deionized water were mixed, and the mixture was stirred at a stirring rate of 240 rpm and room temperature for 24 hours to obtain intermediate b. Commercially available LG BT1001M carbon nanotubes, intermediate b and toluene were mixed and ultrasonically dispersed for 30 minutes, and then the mixture was reacted at a stirring rate of 500 rpm and a temperature of 90°C for 24 hours to obtain modified carbon nanotubes. The ratio of 1-vinylimidazole to n-butane bromide is 0.15 mol: 0.17 mol; the ratio of intermediate a, alanine and deionized water is 0.1 mol: 0.11 mol: 40 mL; the ratio of carbon nanotubes, intermediate b and toluene is 5.7 g: 0.6 g: 50 mL; Step B2: Mix the commercially available party with N303 branched polyether polyol, commercially available sea stone flower PEG400 polyethylene glycol, 1,4-butanediol and isophorone diisocyanate, react for 3 hours at a stirring rate of 120 rpm and a temperature of 90°C, then add hexamethylene diisocyanate, triethylamine and n-hexane, and continue stirring for 30 minutes at a stirring rate of 2400 rpm and a temperature of 50°C, then add deionized water and continue stirring for 30 minutes to obtain a dispersion system, mix the modified carbon nanotubes, diethylenetriamine and deionized water, stir and add to the dispersion system at a stirring rate of 80 rpm and room temperature, and react for 3 hours to obtain foaming microcapsules; The dosage ratio of branched polyether polyol, polyethylene glycol, 1,4-butanediol, isophorone diisocyanate, hexamethylene diisocyanate, triethylamine, n-hexane and deionized water is 0.4g:1g:1.1g:6.5g:4.5g:0.7g:4.2g:70mL; the dosage ratio of modified carbon nanotubes, diethylenetriamine, deionized water and dispersion system is 3.4g:4.2g:15mL:70mL.

[0007] Example 2 A method for preparing a polyurethane electronic adhesive containing n-hexane, comprising the following steps: weighing the following raw materials in parts by weight: 45 parts of polyether polyol, 25 parts of polypropylene glycol, 40 parts of isocyanate, 1 part of 1,4-butanediol, 0.03 parts of catalyst, 6 parts of flame retardant thermal conductive filler, 1.5 parts of foaming microcapsules and 2 parts of foam stabilizer; mixing the polyether polyol, polypropylene glycol, isocyanate, catalyst, flame retardant thermal conductive filler, foaming microcapsules and foam stabilizer, stirring at a stirring rate of 120 rpm and a temperature of 40°C to obtain a polyurethane electronic adhesive containing n-hexane; The polyether polyol is Tangyi RHEOLATE 350D polyether polyol; The polypropylene glycol is Huaxiang PPG-1000 polypropylene glycol; The isocyanate is Wanhua WXB-20180516 isocyanate; The catalyst is Kairui T12 catalyst; The foam stabilizer is Fidelity CAB-35 foam stabilizer; The flame retardant thermal conductive filler is prepared by the following steps: Step A1: Mix commercially available Ruihuang Metal 1000 mesh boron nitride, urea and deionized water and add them to a ball mill, and ball mill for 8 hours at a rotation speed of 800 rpm to obtain precursor 1, mix graphene oxide and deionized water and ultrasonically disperse for 30 minutes, add sodium carbonate solution to adjust the pH value to 8, stir at a stirring rate of 340 rpm and a temperature of 40°C, stir and add precursor 1, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide, and react for 14 hours to obtain precursor 2; The dosage ratio of boron nitride, urea and deionized water is 2.6g:80g:150mL; the mass fraction of sodium carbonate solution is 15%, and the dosage ratio of graphene oxide, deionized water, precursor 1, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide is 1.4g:180mL:2.4g:1.2g:1.5g; Step A2: 1-vinylimidazole and DOPO were mixed, and the mixture was reacted for 12 hours at a stirring rate of 140 rpm and a temperature of 140° C., and then tannic acid, Tris-HCl buffer and ethanol solution were added, and the mixture was cooled to room temperature and reacted for 4 hours, and then ferric chloride and precursor 2 were added and reacted for 12 hours to obtain a flame retardant thermal conductive filler; The mass fraction of the ethanol solution is 15%, the pH value of the Tris-HCl buffer is 8, and the amount ratio of 1-vinylimidazole, DOPO, tannic acid, Tris-HCl buffer, ethanol solution, ferric chloride and precursor 2 is 0.011 mol: 0.011 mol: 6.8 g: 60 mL: 140 mL: 2.2 g: 3.4 g; The foamed microcapsules are prepared by the following steps: Step B1: 1-vinylimidazole and n-butyl bromide were mixed, and the mixture was reacted for 24 hours at a stirring rate of 140 rpm and a temperature of 80°C to obtain an intermediate a. The intermediate a, alanine and deionized water were mixed, and the mixture was stirred for 24 hours at a stirring rate of 240 rpm and room temperature to obtain an intermediate b. Commercially available LG BT1001M carbon nanotubes, intermediate b and toluene were mixed and ultrasonically dispersed for 30 minutes, and then the mixture was reacted for 24 hours at a stirring rate of 550 rpm and a temperature of 90°C to obtain modified carbon nanotubes. The ratio of 1-vinylimidazole to n-butyl bromide is 0.15 mol: 0.18 mol; the ratio of intermediate a, alanine and deionized water is 0.1 mol: 0.11 mol: 40-50 mL; the ratio of carbon nanotubes, intermediate b and toluene is 5.7 g: 0.8 g: 60 mL; Step B2: Mix the commercially available party with N303 branched polyether polyol, commercially available sea stone flower PEG400 polyethylene glycol, 1,4-butanediol and isophorone diisocyanate, react for 3 hours at a stirring rate of 120 rpm and a temperature of 90°C, then add hexamethylene diisocyanate, triethylamine and n-hexane, and continue stirring for 30 minutes at a stirring rate of 280 rpm and a temperature of 50°C, then add deionized water and continue stirring for 30 minutes to obtain a dispersion system, mix the modified carbon nanotubes, diethylenetriamine and deionized water, stir and add to the dispersion system at a stirring rate of 100 rpm and room temperature, and react for 3 hours to obtain foaming microcapsules; The dosage ratio of branched polyether polyol, polyethylene glycol, 1,4-butanediol, isophorone diisocyanate, hexamethylene diisocyanate, triethylamine, n-hexane and deionized water is 0.5g:1g:1.1g:7.2g:4.5g:0.75g:4.2g:75mL; the dosage ratio of modified carbon nanotubes, diethylenetriamine, deionized water and dispersion system is 3.4g:4.2g:18mL:70mL.

[0008] Example 3 A method for preparing a polyurethane electronic adhesive containing n-hexane, comprising the following steps: weighing the following raw materials in parts by weight: 45 parts of polyether polyol, 30 parts of polypropylene glycol, 40 parts of isocyanate, 2 parts of 1,4-butanediol, 0.03 parts of catalyst, 7 parts of flame retardant thermal conductive filler, 1.5 parts of foaming microcapsules and 2 parts of foam stabilizer; mixing the polyether polyol, polypropylene glycol, isocyanate, catalyst, flame retardant thermal conductive filler, foaming microcapsules and foam stabilizer, stirring at a stirring rate of 120 rpm and a temperature of 40°C to prepare a polyurethane electronic adhesive containing n-hexane; The polyether polyol is Tangyi RHEOLATE 350D polyether polyol; The polypropylene glycol is Huaxiang PPG-1000 polypropylene glycol; The isocyanate is Wanhua WXB-20180516 isocyanate; The catalyst is Kairui T12 catalyst; The foam stabilizer is Fidelity CAB-35 foam stabilizer; The flame retardant thermal conductive filler is prepared by the following steps: Step A1: Mix commercially available Ruihuang Metal 1000 mesh boron nitride, urea and deionized water and add them to a ball mill, and ball mill for 10 hours at a rotation speed of 800 rpm to obtain precursor 1, mix graphene oxide and deionized water and ultrasonically disperse for 30 minutes, add sodium carbonate solution to adjust the pH value to 8, stir at a stirring rate of 340 rpm and a temperature of 40°C, stir and add precursor 1, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide, and react for 14 hours to obtain precursor 2; The dosage ratio of boron nitride, urea and deionized water is 2.6g:90g:160mL; the mass fraction of sodium carbonate solution is 15%, and the dosage ratio of graphene oxide, deionized water, precursor 1, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide is 1.5g:180mL:2.6g:1.2g:1.5g; Step A2: 1-vinylimidazole and DOPO were mixed, and the mixture was reacted for 12 hours at a stirring rate of 160 rpm and a temperature of 140° C., and then tannic acid, Tris-HCl buffer and ethanol solution were added, and the mixture was cooled to room temperature and reacted for 4 hours, and then ferric chloride and precursor 2 were added and reacted for 12 hours to obtain a flame retardant thermal conductive filler; The mass fraction of the ethanol solution is 15%, the pH value of the Tris-HCl buffer is 8, and the amount ratio of 1-vinylimidazole, DOPO, tannic acid, Tris-HCl buffer, ethanol solution, ferric chloride and precursor 2 is 0.011 mol: 0.011 mol: 6.8 g: 60-70 mL: 150 mL: 2.2 g: 3.5 g; The foamed microcapsules are prepared by the following steps: Step B1: 1-vinylimidazole and n-butyl bromide were mixed, and the mixture was reacted for 24 hours at a stirring rate of 140 rpm and a temperature of 80°C to obtain an intermediate a. The intermediate a, alanine and deionized water were mixed, and the mixture was stirred for 24 hours at a stirring rate of 260 rpm and room temperature to obtain an intermediate b. Commercially available LG BT1001M carbon nanotubes, intermediate b and toluene were mixed and ultrasonically dispersed for 30 minutes, and then the mixture was reacted for 24 hours at a stirring rate of 550 rpm and a temperature of 90°C to obtain modified carbon nanotubes. The ratio of 1-vinylimidazole to n-butane bromide is 0.16 mol: 0.18 mol; the ratio of intermediate a, alanine and deionized water is 0.11 mol: 0.11 mol: 50 mL; the ratio of carbon nanotubes, intermediate b and toluene is 5.8 g: 0.8 g: 60 mL; Step B2: Mix the commercially available party with N303 branched polyether polyol, commercially available sea stone flower PEG400 polyethylene glycol, 1,4-butanediol and isophorone diisocyanate, react for 4 hours at a stirring rate of 140 rpm and a temperature of 90°C, then add hexamethylene diisocyanate, triethylamine and n-hexane, and continue stirring for 30 minutes at a stirring rate of 280 rpm and a temperature of 50°C, then add deionized water and continue stirring for 30 minutes to obtain a dispersion system, mix the modified carbon nanotubes, diethylenetriamine and deionized water, stir and add to the dispersion system at a stirring rate of 100 rpm and room temperature, and react for 4 hours to obtain foaming microcapsules; The dosage ratio of branched polyether polyol, polyethylene glycol, 1,4-butanediol, isophorone diisocyanate, hexamethylene diisocyanate, triethylamine, n-hexane and deionized water is 0.5g:1.1g:1.2g:7.2g:4.8g:0.75g:4.5g:75mL; the dosage ratio of modified carbon nanotubes, diethylenetriamine, deionized water and dispersion system is 3.6g:4.3g:18mL:75mL.

[0009] Comparative Example 1 Compared with Example 3, this comparative example removes DOPO in the preparation process of the flame retardant thermal conductive filler in Example 3, and the other steps are the same.

[0010] Comparative Example 2 Compared with Example 3, this comparative example is different in that the precursor 2 of Example 3 in the preparation process of the flame retardant and thermally conductive filler of Example 3 is replaced with commercially available Ruihuang Metal 1000 boron nitride, and the other steps are the same.

[0011] Comparative Example 3 Compared with Example 3, this comparative example is different in that the modified carbon nanotubes in Example 3 in the preparation process of the foamed microcapsules in Example 3 are replaced with commercially available LG BT1001M carbon nanotubes, and the other steps are the same.

[0012] The polyurethane electronic adhesives prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were added into a mold and foamed at a temperature of 160° C. to prepare a sample. The thermal conductivity thereof was measured with reference to GB / T 10294-2008. The foamed sealing strip material was made into a 120 mm×10 mm×3 mm sample. With reference to GB / T 10707-2008, the limiting oxygen index and vertical combustion grade thereof were tested. The test results are shown in Table 1 below: Table 1 Test results Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Thermal conductivity (W / (m·K)) 0.607 0.618 0.621 0.614 0.470 0.582 Limiting oxygen index (%) 29.96 30.04 30.18 26.18 29.92 29.45 Vertical burning level V-0 V-0 V-0 V-1 V-0 V-0 It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2 and Comparative Example 3, Comparative Example 1 removes DOPO in the preparation process of the flame retardant and thermally conductive filler of Example 3, and its flame retardant performance is greatly reduced due to the lack of phosphorus element. Comparative Example 2 replaces the precursor 2 of Example 3 in the preparation process of the flame retardant and thermally conductive filler of Example 3 with boron nitride, resulting in a significant decrease in its thermal conductivity. Comparative Example 3 replaces the modified carbon nanotubes of Example 3 in the preparation process of the foamed microcapsules of Example 3 with carbon nanotubes, resulting in a decrease in its thermal conductivity.

[0013] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

Claims

1. A method for preparing polyurethane electronic adhesive containing n-hexane, characterized in that: The method comprises the following steps: weighing the following raw materials in parts by weight: 40-45 parts of polyether polyol, 25-30 parts of polypropylene glycol, 35-40 parts of isocyanate, 1-2 parts of 1,4-butanediol, 0.02-0.03 parts of catalyst, 6-7 parts of flame retardant thermal conductive filler, 1.2-1.5 parts of foaming microcapsules and 1-2 parts of foam stabilizer; mixing the polyether polyol, polypropylene glycol, isocyanate, 1,4-butanediol, catalyst, flame retardant thermal conductive filler, foaming microcapsules and foam stabilizer, stirring at a stirring rate of 120 rpm and a temperature of 40° C. to prepare a polyurethane electronic adhesive containing n-hexane; The flame retardant thermal conductive filler is prepared by the following steps: Step A1: Boron nitride, urea and deionized water are mixed and added to a ball mill, and ball milled for 8-10 hours at a rotation speed of 800 rpm to obtain a precursor 1, graphene oxide and deionized water are mixed and ultrasonically dispersed for 30 minutes, sodium carbonate solution is added to adjust the pH value to 8, and precursor 1, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide are added under stirring at a stirring rate of 300-340 rpm and a temperature of 40°C, and reacted for 12-14 hours to obtain a precursor 2; Step A2: 1-vinylimidazole and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are mixed, and the mixture is reacted for 12 hours at a stirring rate of 140-160 rpm and a temperature of 140° C., and then tannic acid, Tris-HCl buffer and ethanol solution are added, and the mixture is cooled to room temperature and reacted for 3-4 hours, and then ferric chloride and precursor 2 are added and reacted for 12 hours to obtain a flame retardant thermal conductive filler; The foamed microcapsules are prepared by the following steps: Step B1: 1-vinylimidazole and n-butyl bromide are mixed, and the mixture is reacted for 24 hours at a stirring rate of 120-140 rpm and a temperature of 80°C to obtain an intermediate a; the intermediate a, alanine and deionized water are mixed, and the mixture is stirred for 24 hours at a stirring rate of 240-260 rpm and room temperature to obtain an intermediate b; carbon nanotubes, intermediate b and toluene are mixed and ultrasonically dispersed for 30 minutes, and the mixture is reacted for 24 hours at a stirring rate of 500-550 rpm and a temperature of 90°C to obtain modified carbon nanotubes; Step B2: Mix branched polyether polyol, polyethylene glycol, 1,4-butanediol and isophorone diisocyanate, react for 3-4 hours at a stirring rate of 120-140 rpm and a temperature of 90°C, then add hexamethylene diisocyanate, triethylamine and n-hexane, and continue stirring for 30 minutes at a stirring rate of 240-280 rpm and a temperature of 50°C, then add deionized water and continue stirring for 30 minutes to obtain a dispersed system, mix modified carbon nanotubes, diethylenetriamine and deionized water, stir and add to the dispersed system at a stirring rate of 80-100 rpm and room temperature, and react for 3-4 hours to obtain foaming microcapsules.

2. The method for preparing a polyurethane electronic adhesive containing n-hexane according to claim 1, characterized in that: In step A1: the dosage ratio of boron nitride, urea and deionized water is 2.4-2.6g:80-90g:150-160mL; the mass fraction of sodium carbonate solution is 15%, and the dosage ratio of graphene oxide, deionized water, precursor 1, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide is 1.4-1.5g:150-180mL:2.4-2.6g:1.1-1.2g:1.4-1.5g.

3. The method for preparing a polyurethane electronic adhesive containing n-hexane according to claim 1, characterized in that: In step A2: the mass fraction of the ethanol solution is 15%, the pH value of the Tris-HCl buffer is 8, and the amount ratio of 1-vinylimidazole, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tannic acid, Tris-HCl buffer, ethanol solution, ferric chloride and precursor 2 is 0.01-0.011 mol: 0.011 mol: 6.5-6.8 g: 60-70 mL: 140-150 mL: 1.9-2.2 g: 3.4-3.5 g.

4. The method for preparing a polyurethane electronic adhesive containing n-hexane according to claim 1, characterized in that: In step B1: the usage ratio of 1-vinylimidazole and n-butane bromide is 0.15-0.16 mol: 0.17-0.18 mol; the usage ratio of intermediate a, alanine and deionized water is 0.1-0.11 mol: 0.11 mol: 40-50 mL; the usage ratio of carbon nanotubes, intermediate b and toluene is 5.7-5.8 g: 0.6-0.8 g: 50-60 mL.

5. The method for preparing a polyurethane electronic adhesive containing n-hexane according to claim 1, characterized in that: In step B2: the amount ratio of branched polyether polyol, polyethylene glycol, 1,4-butanediol, isophorone diisocyanate, hexamethylene diisocyanate, triethylamine, n-hexane and deionized water is 0.4-0.5g: 1-1.1g: 1.1-1.2g: 6.5-7.2g: 4.5-4.8g: 0.7-0.75g: 4.2-4.5g: 70-75mL; the amount ratio of modified carbon nanotubes, diethylenetriamine, deionized water and dispersion system is 3.4-3.6g: 4.2-4.3g: 15-18mL: 70-75mL.

6. A polyurethane electronic adhesive containing n-hexane, characterized in that: Prepared according to any one of the preparation methods described in claims 1-5.

Citation Information

Patent Citations

  • Preparation method of phase change microcapsule with polyurethane wall material

    CN109126653A

  • Preparation method of foamed microcapsules using polyurethane as wall material

    CN109232962A

  • Preparation method of high-hardness polyurethane electronic glue

    CN117701229A

  • Polyurethane microsphere and preparation method thereof

    CN117801198A

  • Electronic glue containing n-hexane and preparation method thereof

    CN118956323A

Cited By

  • Preparation process of waterborne polyurethane fireproof coating

    CN120505032A

  • Preparation process of water-based polyurethane fireproof coating

    CN120505032B